A Genosensor for Point Mutation Detection of P53 Gene PCR Product Using Magnetic Particles. Issue 6 (14th April 2015) - Hamidi‐Asl, Ezat; Raoof, Jahan Bakhsh; Hejazi, Mohammad Saeid; Sharifi, Simin; Golabi, Seyed Mahdi; Palchetti, Ilaria; Mascini, Marco
Abstract The development of an electrochemical genosensor involving DNA biotinylated capture probe immobilized on streptavidin coated paramagnetic beads and microfluidic based platform for the detection of P53 gene PCR product is reported. The novelty of this work is the combination of a sensitive electrochemical platform and a proper microfluidic system with a simple and effective enzyme signal amplification technology, ELISA, for detection of target DNA sequence and single nucleotide mutation in p53 tumor suppressor gene sequence. The biosensor has been applied to detect the PCR amplified samples and the results shows that it can discriminate successfully perfect matched DNA from mutant form.